2018
DOI: 10.1002/jcp.26750
|View full text |Cite
|
Sign up to set email alerts
|

Zafirlukast promotes insulin secretion by increasing calcium influx through L‐type calcium channels

Abstract: The zafirlukast has been reported to be anti-inflammatory and widely used to alleviate the symptoms of asthma. However, its influence on insulin secretion in pancreatic β-cells has not been investigated. Herein, we examined the effects of zafirlukast on insulin secretion and the potential underlying mechanisms. Among the cysteinyl leukotriene receptor 1 antagonists, zafirlukast, pranlukast, and montelukast, only zafirlukast enhanced insulin secretion in a concentration-dependent manner in both low and high glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, our further results show that the S1P-stimulated [Ca 2+ ] i levels were reduced compared with those observed in Ca 2+ -containing KRB solution in the absence of extracellular Ca 2+ (chelated by EGTA), suggesting S1P markedly increased [Ca 2+ ] i in pancreatic β cells, mainly through extracellular Ca 2 + influx. And other reports support this notion that extracellular Ca 2+ influx via L-VDCC is crucial for regulating [Ca 2+ ] i in β cells (Bokvist, et al, 1995;Hwang, et al, 2018). In our study, patch clamp results showed that the increase in [Ca 2+ ] i is related to the inhibition of Kv channels by S1P, which prolongs the duration of the action potential, indirectly increases voltage dependent Ca 2+ influx, instead of directly affecting VDCC.…”
Section: Discussionsupporting
confidence: 85%
“…However, our further results show that the S1P-stimulated [Ca 2+ ] i levels were reduced compared with those observed in Ca 2+ -containing KRB solution in the absence of extracellular Ca 2+ (chelated by EGTA), suggesting S1P markedly increased [Ca 2+ ] i in pancreatic β cells, mainly through extracellular Ca 2 + influx. And other reports support this notion that extracellular Ca 2+ influx via L-VDCC is crucial for regulating [Ca 2+ ] i in β cells (Bokvist, et al, 1995;Hwang, et al, 2018). In our study, patch clamp results showed that the increase in [Ca 2+ ] i is related to the inhibition of Kv channels by S1P, which prolongs the duration of the action potential, indirectly increases voltage dependent Ca 2+ influx, instead of directly affecting VDCC.…”
Section: Discussionsupporting
confidence: 85%
“…In line with these observations, higher doses of montelukast and zafirlukast are effective in several animal models of CVDs were they showed anti-atherosclerotic effects, protected from myocardial infarction and renal perfusion injury in rabbits, rats and mice (Sener et al, 2006; Jawien et al, 2008; Mueller et al, 2008; Ge et al, 2009; Liu et al, 2009). In addition, during treatment with zafirlukast (20 mg, twice daily) rare cases of hypoglycemic events were observed and it was shown recently that the compound increases insulin secretion from pancreatic β cells (Calhoun et al, 1998; Hwang et al, 2018). These findings concerning the beneficial effects on cardiovascular and diabetic disorders clearly argue for an additional, CysLT-unrelated, mechanism of action which can be exploited for therapy in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Zafirlukast, an antagonist of cysteinyl leukotriene receptor 1 (CysLTR1), is approved for the treatment of chronic asthma as an anti-inflammatory agent and has also been reported to promote insulin secretion [25]. Zafirlukast is a potential hypoglycemic agent that was investigated in this study for its in vitro effects on renal mesangial cells that were cultured with increasing doses of advanced glycation end-products (AGEs).…”
Section: Discussionmentioning
confidence: 99%
“…Zafirlukast is an antagonist of cysteinyl leukotriene receptor 1 (CysLTR1) that is currently prescribed for chronic asthma. Zafirlukast has a dual role in stimulating insulin secretion, and it also has anti-inflammatory effects [16,17]. AGEs that are formed by the glycation of lipids and proteins in conditions of hyperglycemia, including diabetes mellitus, are important inflammatory mediators in diabetes that increase the expression of tumor necrosis factor-a (TNF-a), interleukin-1b (IL-1b), and IL-6, and induce cell apoptosis [13,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation